The Effect of Operating Profit Margin (OPM), Return on Assets (ROA), and Debt-to-Equity Ratio (DER) on Share Prices in Cement Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Fitri wulandari; Aliah Pratiwi; Nurul Huda (GoodWill, 2026)
This study examines the effect of Operating Profit Margin (OPM), Return on Assets (ROA), and Debt to Equity Ratio (DER) on stock prices in cement sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research is motivated by the increasing importance of financial performance indicators in influencing investor decisions and market valuation in the manufacturing sector. This study employs a quantitative associative approach using secondary data obtained from the financial statements of three selected companies, namely PT Semen Indonesia (Persero) Tbk, PT Semen Baturaja Tbk, and PT Indocement Tunggal Prakasa Tbk. The sampling technique used is purposive sampling, resulting in 15 observations. Data were analyzed using multiple linear regression with the assistance of SPSS version 26, supported by classical assumption tests. The findings reveal that partially, OPM and ROA have a positive and significant effect on stock prices, indicating that profitability and asset efficiency are key determinants of firm value. In contrast, DER does not have a significant effect, suggesting that capital structure is less considered by investors in this sector. Simultaneously, OPM, ROA, and DER significantly influence stock prices. The coefficient of determination (R²) shows that 42.3% of stock price variation is explained by the model, while the remaining 57.7% is influenced by other factors. These results provide important implications for investors and corporate managers in optimizing financial performance to enhance market value.